Wenn der Vater fehlt: epidemiologische Befunde zur Bedeutung früher Abwesenheit des Vaters für die psychische Gesundheit im späteren Leben - Franz, Matthias; Schmitz, Norbert; Lieberz, Klaus; Schepank, Heinz (Zeitschrift für psychosomatische Medizin und Psychotherapie, 1999)
SummaryFacing the increasing number of single-parent-families we investigated the impact of fathers absence within the first six years of childhood on psychic/psychosomatic impairment in later life. We used data from the Mannheim Cohort Study on the Epidemiology of Psychogenic (neurotic spectrum) Disorders for a comparison of extreme groups with a favourable or bad course of clinical impairment. In adition we performed regression analysis of the long term course of clinical impairment for the total follow-up sample (mean follow-up intervall 11 years, N=301) with psychometric, clinical and childhood variables. The absence of the probands father (> six months within the first six years of life) was a significant independend predictor of clinical impairment in later life, accompanied by clinical and psychometric variables. A significant and increasing impairment existed even in 73 of 125 older probands (birth cohort 1935), who missed their father in early childhood. The sociopolitical implications of these findings are discussed.